1990
DOI: 10.1007/bf01966460
|View full text |Cite
|
Sign up to set email alerts
|

The influence of histamine and PGE2-induced hyperaemia and oedema on respiratory metabolism in normal human forearm skin

Abstract: Transcutaneous measurements of pO2 and pCO2 were made on the forearm skin after intradermal injection of histamine, PGE2, and saline. The mediators, used at concentrations which induce intense hyperaemia, did not modify the steady state tcpO2/pCO2 levels measured with a sensor head temperature of 44 degrees C when breathing air or hyperbaric (2ATA) oxygen. It was deduced that gas transport is unaffected by mediator-induced conditions in the skin. The rates of fall of tcpO2 and of rise of tcpCO2 after arresting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…14 By increasing the distance between capillaries and target tissues, oedema may directly reduce oxygen and nutrient exchange and significantly impair skin metabolism. 10,12,36 Oedema could cause a rise in mechanical tissue tension and pressure, which ultimately causes tissue ischaemia, necrosis and ulceration. 13 Furthermore, in older people (patient ages: 53-75 years, median 62 in the present study) the skin is less elastic and less compliant, oedema cannot be easily accommodated and skin tension rises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 By increasing the distance between capillaries and target tissues, oedema may directly reduce oxygen and nutrient exchange and significantly impair skin metabolism. 10,12,36 Oedema could cause a rise in mechanical tissue tension and pressure, which ultimately causes tissue ischaemia, necrosis and ulceration. 13 Furthermore, in older people (patient ages: 53-75 years, median 62 in the present study) the skin is less elastic and less compliant, oedema cannot be easily accommodated and skin tension rises.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] So far, various theories have been developed to explain why oedema is associated with venous leg ulcers, and some studies have demonstrated that the oedema in the papillary dermis, a site of intensive metabolism in the skin, might be a more important mechanism underlying tissue injury and ulceration. [9][10][11][12][13][14][15][16] Because of this, new techniques to investigate the distribution of oedema in the skin are important.…”
mentioning
confidence: 99%
“…Possibly, more common than the assessment of cardiac failure is the evaluation of the degree of hydration in a patient. A fast quantitative method of monitoring the fluid balance of a patient would be a useful tool in the hospital emergency room to help avoid the risks associated with intravenous rehydration of the dehydrated patient [previous work has shown that oedema due to over‐hydration can lead to venous eczema and ulceration, as the excess fluid increases the distance between tissue cells (41), reducing oxygen consumption (42, 43)]. The proposed device could fulfil this requirement by tracking changes in the viscoelastic properties in a particular patient over time.…”
Section: Discussionmentioning
confidence: 99%